The role of media and peer influences in Australian women's attitudes towards cosmetic surgery - Sharp, Gemma; Tiggemann, M.; Mattiske, J. (Elsevier BV, 2014)
The study aimed to examine the influence of media and peers on attitudes towards cosmetic surgery using a sociocultural framework. A sample of 351 Australian women aged 18–69 years completed measures of media exposure, friend conversations, internalisation of appearance ideals, appearance comparison, body dissatisfaction, and attitudes towards cosmetic surgery. Correlational analysis showed that almost all media and friend variables were significantly correlated with positive attitudes towards cosmetic surgery. A structural equation model based on the sociocultural model showed a good level of fit to the data. The effects of media exposure and friend conversations on body dissatisfaction and attitudes towards cosmetic surgery were mediated by internalisation. We concluded that media exposure and friend conversations affected attitudes towards cosmetic surgery both directly and indirectly. Our results contribute to the understanding of the sociocultural mechanisms underlying women's motivations for cosmetic surgery.